DAKWAH DIGITAL DALAM PERSFEKTIF MAD’U (AUDIENS) - Badrudin Kamil (AT-TAWASUL, 2022)
Da'wah is an activity carried out by every Muslim religious leader in conveying Islamic law contained in both the Qur'an and the Sunnah of the Prophet Muhammad. In conveying this revelation, usually not every person who equates it needs expertise and skills in conveying it, especially requiring a deep understanding of religion in each of the contents of the message. The existence of the role of the mass media facilitates the delivery of messages that used to be orally orally to be not limited by distance and time. New media is not only done for negative things. New media can also act as positive media, especially in spreading goodness through da'wah. The media that is often used in this modern era is social media. Social media is a communication medium that almost all people in the world use. This new media used for preaching also functions as a public space. Information containing Islamic religious values ​​created by these da'i can be responded to directly by mad'u, so that public space can be created in the new media. Social media, which is included as a new media, has a positive impact in spreading goodness. Da'wah using this new media has a significant role in increasing mad'u motivation. The da'i's creativity in using this new media attracted the interest of mad'u to want to apply Islamic values ​​in their lives.